Stereotyping of Conditional and Imperative Suffixes in Kipchak Group Turkish Dialects - Üstüner, Ahat; Yavi, Fecri (Ege University, 2023)
Stereotyping of inflectional suffixes, form permanent word types by fusing inflectional suffixes to nouns or verbs with different functions, apart from their existing duties due to any number of reasons, and according language’s own needs. New words are added to vocabulary of Turkish language by means of linguistic stereotyping – i.e. a multi-faceted, non-generalisable, unrestricted, and common product(s) of semantics and linguistics. The word derivation function of inflectional suffix stereotypes – as is the case with derivational suffixes – is neither regular nor systematic. Therefore, it seems more logical to refer to word derivations made from stereotyping as exceptional derivations. In this study, we examined word derivations with example sentences using stereotyped conditional and imperative suffixes in Kipchak group Turkish dialects in the context of causality, and determined words derived as a result of stereotyping and investigated them in terms of structure and meaning. Although permanent words that can be dictionary units are not derived in Turkish with verb conjugation suffixes, it is seen that these suffixes take place in the structure of some permanent words as a result of stereotyping. It was also determined that in Kipchak group, words derived as a result of stereotyping of the imperative suffixes are mainly exclamatory words and they derive a small handful of words in the form of prepositions, conjunctions and adjectives. Words derived as a result of stereotyping of conditional suffix are generally conjunctions and adverbs. This suffix appears in the structure of a small number of nouns, pronouns, exclamations, and adjectives. This study, which was conducted in order to understand the contribution of inflectional suffix stereotypes to the vocabulary of Turkish language, will also shed light on the studies to be carried out on word formation in Turkish.

Çekim eki kalıplaşmaları, isim veya fiil çekim eklerinin çeşitli nedenlere ve dilin kendi ihtiyaçlarına bağlı olarak görevlerinin dışında eklendiği kelimeyle kaynaşarak kalıcı sözcükler türetmeleridir. Bu kalıplaşmalarla Türkçenin söz varlığına çok yönlü, genellenemeyen, sınırlandırılamayan ve anlam bilimi ile dil biliminin ortak ürünleri olan yeni sözcükler eklenir. Çekim eki kalıplaşmalarının sözcük türetme işlevi, yapım eklerindeki gibi kurallı ve sistematik değildir. Bu yüzden kalıplaşmalarla yapılan türetmelere, kural dışı türetmeler demek daha mantıklı görünmektedir. Bu çalışmada Kıpçak grubu Türk lehçelerinde şart kipi ve emir kipi eklerinin kalıplaşarak sözcük türetmeleri, nedensellik bağlamında ve örnek cümlelerle incelenmiştir. Türkçede fiil çekim ekleriyle sözlük birimi olabilecek kalıcı sözcükler türetilmemesine rağmen, kalıplaşmalar sonucu bu eklerin bazı kalıcı sözcüklerin yapısında yer aldıkları görülür. Kıpçak grubu Türk lehçelerinde emir kipi eklerinin kalıplaşmasıyla oluşan sözcüklerin daha çok ünlem türünden sözcükler olduğu, bunların az sayıda edat, bağlaç ve sıfat türünden sözcükler türettiği de tespit edilmiştir. Bu lehçe grubunda şart ekinin kalıplaşmasıyla oluşan sözcüklerin de genellikle bağlaç ve zarf türünden sözcükler olduğu görülür. Aynı zamanda bu ek az sayıda isim, zamir, ünlem ve sıfat görevli sözcüğün yapısında yer almaktadır. Çekim eki kalıplaşmalarının Türkçenin söz varlığına katkısını anlayabilmek için yapılan bu çalışma, Türkçede söz yapımı üzerine yapılacak incelemelere ışık tutacaktır. Araştırmada Kıpçak grubu Türk Lehçelerinde adı geçen çekim eklerinin kalıplaşmasıyla oluşmuş pek çok sözcük belirlenerek, bu sözcükler yapı ve anlam bakımından incelenmiştir.
Kıpçak Grubu Türk Lehçelerinde Şart ve Emir Eklerindeki Kalıplaşmalar
Keywords: Literary Studies (Other); Edebi Çalışmalar (Diğer)